The Obligation to Provide Iddah Maintenance in Article 152 of the Compilation of Islamic Law - Rosihin Rosihin; Syamsu Madyan; Nur Hasan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
As stipulated in Islam, marital responsibilities will remain even after the marriage ends. Therefore, the term